Revision of the genus Ateralphus Restello, Iannuzzi & Marinoni, 2001 (Coleoptera: Cerambycidae: Lamiinae) - Souza, Diego De S.; Monné, Marcela L. (Zootaxa, 2013)
A revision of the genus Ateralphus Restello, Iannuzzi & Marinoni, 2001, based on the detailed study of the morphology of the type-species and on the external morphology and terminalia of the others species is presented. The genus and species are redescribed and three new species are described. The genus is composed of nine species: A. dejeani (Lane, 1973), A. javariensis (Lane, 1965), A. lacteus Galileo & Martins, 2006, A. senilis (Bates, 1862), A. subsellatus (White, 1855), A. variegatus (Mendes, 1938), A. auritarsus new species, A. lucianeae new species and A. tumidus new species. A key for identification of the species and maps of their geographical distribution are provided.